Comparison between Insulin Glargine and Insulin Detemir in Adolescents with Type 1 Diabetes during Ramadan Fasting - Kaplan, Walid; Afandi, Bachar; Al Hassani, Noura (Journal of Diabetes and Endocrine Practice, 2022)
Objectives The aim of this study was to compare between insulin glargine and insulin detemir on glucose profile in adolescents with type 1 diabetes mellitus (T1DM) who fast the month of Ramadan.Materials and Methods This was prospective, cross-over study. Subjects were randomized into Group G, in which insulin glargine was given once daily, and Group D, in which ⅔ of the total dose of insulin detemir was given before breaking the fast and ⅓ before starting it. Subjects were crossed-over after 1 week. We compared the mean interstitial glucose (IG), and the percentages of hypoglycemia (<70mg/dL) and severe hyperglycemia (>300mg/dL) between the groups.Results A total of 11 adolescents were enrolled. Mean (±standard deviation) age was 14±3.3 years. There was no difference in the mean IG (190±46 vs. 198±37mg/dL, p=0.1), or the percentages of severe hyperglycemia (13.5±12.9% vs. 13.6±9.2%, p=0.5) in group G and Group D, respectively. Conversely, the percentage of hypoglycemia was higher in Group G than Group D (9.1±7.0% vs. 4.4±2.7%, respectively, p=0.01).Conclusion Insulin detemir given twice daily results in less hypoglycemia than once daily insulin glargine in adolescents with T1DM during fasting in Ramadan.
Keywords: adolescents; detemir; glargine; Ramadan fasting